Citizen power : a citizen leadership manual introducing the art of no-blame problem solving - Pozycki, Harry S. (Rutgers University Press, 2020)
"The Citizens Campaign, co-founded by the author and his wife, Caroline B. Pozycki, offers citizen leadership training and citizen leadership service opportunities for regular citizens. CITIZEN POWER gives all Americans the know how to become no-blame problem solvers and be part of what is emerging as a new model for a citizen driven national public service"--